Asian REITS: Growing into maturity - Ooi, Joseph T. L.; Wong, Woei Chyuan (Springer Berlin Heidelberg, 2013)
The Asian REIT markets have grown substantially over the past decade, partly due to a boom in the number of REIT IPOs and partly due to the newly listed REITs expanding aggressively by acquiring many properties within a short time period, often funded by cheap debt. Investors’ appetite is boosted by the positive risk-adjusted returns registered in the four major REIT markets in Asia, namely Japan, Singapore, Hong Kong and Malaysia.